1967
DOI: 10.1530/acta.0.0540311
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Antiserum to Purified Gonadotrophins From Rat Pituitary Glands

Abstract: Antiserum to a gonadotrophic extract of rat pituitary glands was prepared and investigated: In specific assays the antiserum neutralized rat FSH and LH, as well as the total gonadotrophic effect measured by the mouse uterus test. The antiserum did not counteract the gonadotrophic activity of HMG and HCG, but inhibited endogenous mouse gonadotrophins. The antiserum interrupted the continuous oestrous cycle in androgen sterilized rats. When antiserum was injected into mature female rats starting on the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1969
1969
1979
1979

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Littermate newborn ICR Swiss-Albino mice were used in all experiments. One group was injected with 0-1 ml antiserum to rat gonadotrophins (aRG) (Lunenfeld, Eshkol, Baldratti & Suchowsky, 1967) daily up to the age of 10 days. A second group received daily injections of aRG plus biologically pure human FSH devoid of LH activity , while the control animals were given 0-1 ml normal rabbit serum daily.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Littermate newborn ICR Swiss-Albino mice were used in all experiments. One group was injected with 0-1 ml antiserum to rat gonadotrophins (aRG) (Lunenfeld, Eshkol, Baldratti & Suchowsky, 1967) daily up to the age of 10 days. A second group received daily injections of aRG plus biologically pure human FSH devoid of LH activity , while the control animals were given 0-1 ml normal rabbit serum daily.…”
Section: Methodsmentioning
confidence: 99%
“…We have carried out ultrastructural analyses in an attempt to determine to what extent substitution with FSH could prevent the developmental changes observed following deprivation of both gonadotrophic hormones (LH plus FSH) in mice. Deprivation was achieved by neutralizing the endogenous gonadotrophins with rabbit anti-rat gonadotro¬ phins (Lunenfeld, Eshkol, Baldratti & Suchowsky, 1967).…”
Section: Introductionmentioning
confidence: 99%
“…Rat LH assay reagents obtained from the NIAMDD, NIH Rat Pituitary Hormone Distribution Program, Bethesda, Maryland, U.S.A., were used and LH values are expressed as ng NIAMDD-rat-LH-RP-1/ml. A radioimmunoassay for rat LH was used as Lunenfeld, Eshkol, Baldratti & Suchowsky (1967) had previously precipitated mouse LH by using a rat anti-LH antibody. A preliminary trial with the NIAMDD rat reagents using serum from male mice of the TO strain showed good cross-reaction with the antibody.…”
Section: Gonadotrophin Assaymentioning
confidence: 99%
“…Antiserum to sheep gonadotropins was inappropriate due to its broad spectrum of cross reactions (table I). Antiserum to bovine gonadotropins also exhibits reac tivity with gonadotropins of many species including man [42], Antiserum to rat pituitary gonadotropins has been prepared and charac terized by Lunenfeld et al [28]. This antiserum neutralized the biological effects of rat pituitary FSF1 and LH and cross-reacted with endogenous mouse gondadotropins.…”
Section: Effects O F Gonadotropic Deprivation and Specific Gonadotropmentioning
confidence: 99%